Vitamins as Possible Cancer Biomarkers: Significance and Limitations - Sascha Venturelli (MDPI AG, 2021)
The Western-style diet, which is common in developed countries and spreading into developing countries, is unbalanced in many respects. For instance, micronutrients (vitamins A, B complex, C, D, E, and K plus iron, zinc, selenium, and iodine) are generally depleted in Western food (causing what is known as ‘hidden hunger’), whereas some others (such as phosphorus) are added beyond the daily allowance. This imbalance in micronutrients can induce cellular damage that can increase the risk of cancer. Interestingly, there is a large body of evidence suggesting a strong correlation between vitamin intake as well as vitamin blood concentrations with the occurrence of certain types of cancer. The direction of association between the concentration of a given vitamin and cancer risk is tumor specific. The present review summarized the literature regarding vitamins and cancer risk to assess whether these could be used as diagnostic or prognostic markers, thus confirming their potential as biomarkers. Despite many studies that highlight the importance of monitoring vitamin blood or tissue concentrations in cancer patients and demonstrate the link between vitamin intake and cancer risk, there is still an urgent need for more data to assess the effectiveness of vitamins as biomarkers in the context of cancer. Therefore, this review aims to provide a solid basis to support further studies on this promising topic.